The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1983-21252019v32n413rc
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Quality as a Function of Seed Clove Health and Size and Spacing Between Plants

Abstract: Garlic has a worldwide economic importance; this vegetable can be consumed fresh or processed by food industries. However, few studies evaluate its postharvest quality. It is necessary to establish cultural practices and methods that focus not only on increase of yield, but on obtaining a product with better postharvest quality. The objective of this work was to evaluate the bulb quality of conventional garlic and virus-free garlic as a function of seed clove size and space between plants. Two experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
5
6
0
Order By: Relevance
“…These results are consistent with those found in other studies (BIESDORF et al, 2015;MARODIN;SOUZA, 2018;LIMA et al, 2019), that showed larger bulb diameter for VFGC when compared to infected cultivars.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…These results are consistent with those found in other studies (BIESDORF et al, 2015;MARODIN;SOUZA, 2018;LIMA et al, 2019), that showed larger bulb diameter for VFGC when compared to infected cultivars.…”
Section: Resultssupporting
confidence: 93%
“…Differences in SS between cultivars may be caused by seed genetic characteristics and crop environment (LIMA et al, 2019). Mota et al (2003) found 34% and 37.16% SS in the infected cultivars Cateto-Roxo and Amarante, respectively, which are similar results to those obtained in the present work.…”
supporting
confidence: 90%
See 3 more Smart Citations